Peran Komunikasi Organisasi Dalam Meningkatkan Eksistensi Lembaga Amil Zakat Infaq Shadaqah Muhammadiyah (Lazismu) Kota Palembang - Nur Indah Farizka Febrianti; Hamidah; Hidayat (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This research is entitled "The Role of Organizational Communication in Improving the Existence of Amil Zakat, Infaq, Sadaqah Muhammadiyah Institutions Palembang City". This study aims to determine the role of organizational communication in achieving organizational goals to increase the existence of LAZISMU Palembang City. The method used in this study is a qualitative research method using data sources, namely primary and secondary data consisting of 8 (eight) research informants. Then this study used data collection techniques in the form of through the stages of observation, in-depth interviews and documentation with data analysis techniques carried out with several processes where the researcher carried out data reduction and data presentation so that conclusions could be drawn from the research. This research is based on the theory of Daniel Katz and Robert L.Khan in Arni Muhammad's book entitled Organizational Communication, which then results from the theory and research conducted previously that organizational communication acts as a vessel for realizing organizational expectations or goals. LAZISMU Palembang City, organizational communication also has an important role as the main key in the organization because organizational communication from LAZISMU Palembang City acts as a mediator for the leadership and management staff of the institution in providing various opinions, suggestions, ideas and criticism. Organizational communication also plays an important role in increasing the productivity and quality of performance of the leadership and managing staff of the institution where communication must always be prioritized. Organizational communication plays an important role in carrying out internal and external activities within LAZISMU Palembang City and is fundamental for the smooth operation of this institution.